# Simplify 4-3i / i

### 2 Answers | Add Yours

`(4-3i)/i=(4-3i)i/i^2=` `-(4i+3)`

The answer to `4-3i/i` is obviously 1 whether you simplify using rules or just cross-cancel. Please take care to bracket the expression so that it is clearly understood. So to answer

`(4-3i)/i`

Multiply by `i/i`

`therefore (4i - 3i^2)/(i^2)` We know that `i=sqrt(-1) and i^2=-1`

`therefore =(4i - 3(-1))/-1`

`therefore = (4i +3)/-1`

`therefore = (4i)/-1 +3/-1`

**Ans: **`therefore = -4i - 3` OR

**Ans: `= -(4i+3)` **